SPES/PVDF/TPA composite membrane as an alternative proton exchange membrane in vanadium redox flow battery application. (April 2018) - Lian, Xiaojuan; Yang, Xin; Liu, Hongdong; Liu, Haitao; Zhu, Jiang
A new kind of composite membrane consisting of sulfonated poly(ether sulfone) (SPES), poly(vinylidene fluoride) (PVDF), and phosphotungstic acid (TPA) has been prepared and employed as the ion-exchange membrane for vanadium redox flow battery (VRB) application. The addition of the highly crystalline and hydrophobic PVDF effectively confines the swelling behavior of SPES/PVDF/TPA. The composite membrane exhibits one order of magnitude lower vanadium ions permeability and much better single cell performance compared to pristine SPES and Nafion 115 membranes. The single cell with SPES/PVDF/TPA membrane shows much lower capacity loss, higher coulombic efficiency (>97%), and higher energy efficiency (>82%) than which with Nafion 115 membrane. In the self-discharge test, single cell with SPES/PVDF/TPA membrane shows much longer duration in the open-circuit voltage decay than which with Nafion 115 membrane. With all the good performances and low cost, the SPES/PVDF/TPA membrane is expected to have excellent commercial prospects as ion-exchange membrane for VRB system.